The Effect of Contextual Teaching and Learning (CTL) Assisted by Audiovisual Media on Students’ Cognitive Achievement and Learning Interest in Colloid Topics - Mutiara Mutiara; Isna Rezkia Lukman; Ucia Mahya Dewi; Ayu Rahmi; Fakhrah Fakhrah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigated the effect of the Contextual Teaching and Learning (CTL) instructional model supported by audiovisual media on students’ cognitive achievement and learning interest in the colloid topic at SMA Negeri 1 Syamtalira during the 2024/2025 academic year. A quantitative approach employing a quasi-experimental method with a non-equivalent control group design was adopted. The participants were selected through purposive sampling, consisting of 29 students from class XI IPAS 8 as the experimental group and 30 students from class XI IPAS 7 as the control group. Data were collected using a cognitive achievement test and a learning interest questionnaire. Statistical analysis was conducted using an independent samples t-test. The findings revealed that students taught using the CTL model integrated with audiovisual media demonstrated significantly higher cognitive achievement and learning interest than those taught using the Discovery Learning model. The experimental group achieved a higher mean posttest score (79.31) compared to the control group (63.78). In addition, the average learning interest score of the experimental group reached 84% (very high category), while the control group obtained 78% (high category). The t-test results showed a Sig. (2-tailed) value of 0.000 ( 0.05), indicating a statistically significant effect of the CTL model supported by audiovisual media on students’ cognitive achievement and learning interest in colloid learning.